Carex flava agg. (section Ceratocystis, Cyperaceae) in Poland: distribution maps and locality lists - Więcław, Helena (Biodiversity: Research and Conservation, 2015)
This paper presents lists of localities and distribution maps of Carex taxa of the section Ceratocystis in Poland. Distribution maps of individual taxa are based on the ATPOL grid, using material deposited in Polish herbaria and private collectionsas well as material collected during field research in 2007-2012. The collected data indicate that (i) in Poland C. flava s.s. is the most common species of the section Ceratocystis, whereas C. hostiana is the rarest one; (ii) most of the localities of C. demissa are situated in southern Poland, especially in Małopolska, Podkarpacie, and Silesia Provinces (iii) C. lepidocarpa is most frequent in Polesie, Lublin Upland, Małopolska, and Pomerania; no records of this species in southernmost parts of Poland have been confirmed; (iv) C. viridula var. viridula is frequent in Poland, whereas C. viridula var. pulchella is only known from 2 localities in the north; (v) the most frequent hybrid in Poland is C. ×alsatica [C. demissa × C. flava], while C. ×ruedtii [C. flava × C. lepidocarpa], C. ×subviridula [C. flava × C. viridula], and C. ×schatzii [C. lepidocarpa × C. viridula] are reported less often; the rarest hybrids are C. demissa × C. viridula, C. ×fulva [C. demissa × C. hostiana], and C. ×leutzii [C. hostiana × C. lepidocarpa].